Effectiveness of aspiration or deroofing for blister management in patients with burns: A prospective randomized controlled trial. Issue 17 (April 2018) - Ro, Hyung-Suk; Shin, Jin Yong; Sabbagh, Mohamed Diya; Roh, Si-Gyun; Chang, Suk Choo; Lee, Nae-Ho
Abstract: Background: Health care providers commonly encounter blisters when treating burn patients. The question as to whether burn blisters should be drained or deroofed has long been debated. To our knowledge, there has been no controlled, randomized clinical trial to determine which treatment is the best management option. Methods: Between March 2016, and September 2016; 40 patients with burn blisters greater than 6-mm were enrolled in our study. Patients were randomized into 2 groups: aspiration group and deroofing group. The number of days to complete re-epithelialization was noted. Patient and Observer Scar Assessment Scale data were recorded from subjects and investigators at 4 time points. Pain during dressing changes was evaluated using a visual pain scale. Bacterial cultures were also obtained. Results: Average number of days to complete wound healing was 12 days in the aspiration group and 12.55 days in deroofing group. On the Patient and Observer Scar Assessment Scale, investigators found that the aspiration group scars demonstrated improvements in relief and thickness while subjects rated aspiration scars better in terms of pain. Patients with palm/sole blister in the deroofing group scored higher than aspiration group on the visual analogue pain score but it was also not statistically significant (2.66 vs 3.25). The overall incidence of colonization with microorganisms in each group was not significant (15% vs 40%). Conclusion: Neither aspiration nor deroofing is a superior treatment of burn blister. However, some objective indicators suggest that aspiration treatment might be more effective than deroofing treatment.